The salt tolerance of vegetable paprika varieties - Slezák, K.; Terbe, I.; Kappel, N.; Tóth, K. (International Journal of Horticultural Science, 2003)
In our experiments, we have chiefly tested the salt sensitivity of sweet pepper varieties. In cold forcing, 0.3 1/plant nutrient solutions of different NaCI content were given twice weekly. EC of the nutrient solutions containing 0.25% Volldünger Linz complex fertilizer was made up to 6, 10, 14 and 18 mS/cm, respectively, by 2.51/9.17/17.97/26.76 g/m2 doses of pharmacopeal NaCI every week. The solution used for the control treatment contained Volldünger only (EC 4.4 mS/cm). Irrigation was made with pure water (EC 0.6 mS/cm) when necessary. The varieties chosen for the experiments were the following: Feherözön, HRF F1, Syn. Cecei (of white, conical fruit), Boni (of white, blunt, infolded fruit), Titan F1 (of pointed, hot fruit) and Pritavit F1 (of tomato shaped fruit). In general, the symptoms caused by NaCI treatments (with doses higher than 10 g/m2 weekly) have been the following: • They have reduced the leaf area, the height of the plants, the total and the early yield, the number of fruit set per square meter, the average weight of the fruit (and, in some measure, fruit length, too) and the thousand seed weight. • They have increased the calcium and the chlorine content of the leaves and fruits and the dry matter content of the fruits. • They haven’t affected the dry matter content of the leaves, the nitrogen, phosphorus and potassium content of the leaves and fruits, and the germinating ability of the seed. • The effect on stem diameter and on seed production per fruit has been contradictory in some cases. The effects of the intermediate treatments haven’t been explicit in several cases. The results of the examination of cuticular secretion have indicated the increase of the sodium and chlorine content of the leaves. This can be important in field growing where the rainwater may wash out a part of sodium and chlorine from paprika leaves. The hot, pointed variety and the tomato shaped paprika haven’t shown clearly higher salt tolerance than the varieties of white fruit colour.